If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying log(9x + 7) = 2 Reorder the terms: glo(7 + 9x) = 2 (7 * glo + 9x * glo) = 2 (7glo + 9glox) = 2 Solving 7glo + 9glox = 2 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Reorder the terms: -2 + 7glo + 9glox = 2 + -2 Combine like terms: 2 + -2 = 0 -2 + 7glo + 9glox = 0 The solution to this equation could not be determined.
| -11-5=10-8x | | 12x^4-7x^2=0 | | 3x^2+19x=28 | | 3x+1=-1 | | -4[2(x-7)+3]+20= | | 2n=0.5+30 | | r-(-3)=3 | | 4x-2-2x=6x-4 | | 4x^2+17x=15 | | r+3=3 | | r-6=-13 | | 3x-9/4=6 | | 4-r=1 | | 12(2x-1)/6=24 | | f+9=6 | | 5-6p+3p-8= | | 22+4x=3-7+2x | | 3-(6x+9)-10x=1 | | 10-2t+6t=t+22 | | 4(2y+9)+7y=24 | | 5(3x-7)=5 | | 7=-3(5+2q) | | 20=d+16 | | 7(x-5)/3=14 | | 235=pi*10*l | | 3x+5(4x-7)=2-(2x+8) | | 4x-5+2=5 | | 2v+3(8-v)=16 | | x^2-36x+27=0 | | x-4/6=4 | | -8n-33=-8-4(2n+6) | | -2+6-s-4= |